Accelerating 2d fault diagnosis of an induction motor using a graphics processing unit - Uddin, Jia; Van, Dinh Nguyen; Kim, Jong-Myon (© 2015 Science and Engineering Research Support Society, 2016)
This article was published in the Journal of Applied Mathematics [© 2015 SERSC] and the definite version is available at :http://dx.doi.org/10.14257/ijmue.2015.10.1.32 The Journal's website is at:http://www.sersc.org/journals/IJMUE/vol10_no1_2015/32.pdf